Improved survival after LTx‐associated acute GVHD with mAb therapy targeting IL2RAb and soluble TNFAb: Single‐center experience and systematic review. Issue 12 (23rd June 2018) - Minnee, R. C.; Fieuws, S.; Jochmans, I.; Aerts, R.; Sainz Barriga, M.; Debaveye, Y.; Maertens, J.; Vandenberghe, P.; Laleman, W.; van der Merwe, S.; Verslype, C.; Cassiman, D.; et al.
Abstract : Acute graft‐versus‐host disease (GVHD) after liver transplant (LTx) is a rare complication with a high mortality rate. Recently, monoclonal antibody (mAb) treatment, specifically with anti–interleukin 2 receptor antibodies (IL2RAb) and anti–tumor necrosis factor‐α antibodies (TNFAb), has gained increasing interest. However, evidence is mostly limited to case reports and the efficacy remains unclear. Here, we describe 5 patients with LTx‐associated GVHD from our center and provide the results of our systematic literature review to evaluate the potential therapeutic benefit of IL2RAb/TNFAb treatment. Of the combined population of 155 patients (5 in our center and 150 through systematic search), 24 were given mAb (15.5%)—4 with TNFAb (2.6%) and 17 with IL2RAb (11%) ("mAb group")—and compared with patients who received other treatments (referred to as "no‐mAb group"). Two‐sided Fisher exact tests revealed a better survival when comparing treatment with mAb versus no‐mAb (11/24 vs 27/131; P = .018), TNFAb versus no‐mAb (3/4 vs 27/131; P = .034), and IL2RAb versus no‐mAb (8/17 vs 27/131; P = .029). This systematic review suggests a beneficial effect of mAb treatment and a promising role for TNFAb and IL2RAb as a first‐line strategy to treat LTx‐associated acute GVHD. Abstract : This cases series and systematic review reveals a beneficial effect of monoclonal antibody treatment and a promising role for anti‐TNF‐α antibody and anti‐interleukin‐2 receptor antibody to treat liver transplantation–associated acute graft‐versus‐host disease as a first‐line strategy.